LOOKING FOR THE E-COMMERCE QUALITY CRITERIA: DIFFERENT PERSPECTIVES - Guseva, Natalija (Ekonomika, 2011)
To assure a successful development of e-commerce, it is necessary to define the criteria that could guide the choice of a competitive e-commerce system and its quality evaluation. The aim of this study was to bring together and analyze the e-commerce quality criteria proposed in the scientific literature, by e-commerce experts, and important for customers. Analysis allowed to identify a triple set of e-commerce quality criteria, as well as the differences among the criteria provided by invoked sources.